A redescription of Ribautia picturata Lawrence, 1960, a little known geophilid centipede from Madagascar (Myriapoda: Chilopoda: Geophilomorpha) - Pereira, Luis Alberto (2010)
The geophilomorph centipede Ribautia picturata Lawrence, 1960 from Madagascar is redescribed and illustrated based on the type material preserved in the collections of the Muséum national d’Histoire naturelle in Paris. The original generic allocation of the species is confirmed. A distribution map is also provided for the taxon. Morphological traits of R. picturata apparently do not identify it as particularly similar to the species, or species groups of Ribautia, inhabiting a given geographic area. Phylogenetic and biogeographic affinities cannot be established until appropriate and comprehensive analyses of the genus are performed.